Estresse calórico sobre a luteólise de vacas holandesas não lactantes - Mogollón García, Henry David [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objective was to study the main genes associated with the production, maintenance and regression of the corpus luteum (CL) and correlate the findings with the production of progesterone in non-lactating Holstein cows, besides clarifying physiological mechanisms involved in the response to heat stress. The cows were synchronized with CIDR-SYNCH protocol and randomly distributed in two environments: thermoneutral (n = 12), temperature 24 ° C, humidity 50%; heat stress (n = 12), temperature 38 ° C, humidity 70%. The D0 was defined as the day of the second application of GnRH. In each environment three different treatments were performed and in D7, for each treatment 4 cows were used. Treatment 1: 2 ml saline; Treatment 2: 25 mg Lutalyse®; and Treatment 3: 12.5 mg Lutalyse®. The degree of heat stress was determined by the temperature and humidity index. Blood samples were obtained for determining plasma concentrations of progesterone (P4) by chemiluminescence immediately before and every 6 hours after treatment with PGF2α, until 24 hours. Subsequently, the collection was performed every 12 hours up to 48 hours. The respiratory rate, heart rate and rectal temperature were measured every 12 hours for 7 days; vaginal temperature was determined over 7 days with readings every 10 minutes. The respiratory rate, rectal and vaginal temperature were higher in heat stress environment when compared to thermoneutral (P <0.05). Heart rate did not differ between the two environments (P> 0.05). There was no difference (P> 0.05) in the concentration of P4 when the environments and their respective treatments were compared. However, when evaluating individually the environments, it was observed that the cows who received the treatment with ½XPGF2α in heat stress and thermoneutral environment showed an initial P4 decrease up to 18 hours with subsequent recovery, showing a partial luteolysis. This fact demonstrates that heat stress caused no ...

O objetivo do trabalho foi estudar os principais genes associados à produção, manutenção e regressão do corpo lúteo (CL) e correlacionar os achados com a produção de progesterona em vacas holandesas não lactantes. As vacas foram sincronizadas com o protocolo CIDR-SYNCH e distribuídas aleatoriamente em dois ambientes: termoneutro (n = 12) com temperatura 24°C e umidade 50%, estresse calórico (n = 12) com temperatura 38°C e umidade 70%. O dia zero (D0) foi definido como o dia da segunda aplicação de GnRH, em cada ambiente foram conformados tres tratamentos diferentes ao D7, para cada tratamento foram empregadas 4 vacas,: tratamento 1: 2 mL solução salina; tratamento 2: (25 mg) de Lutalyse® ; e tratamento 3: (12,5 mg) de Lutalyse®. O grau de estresse calórico foi determinado pelo índice de temperatura umidade. Concentrações plasmáticas de progesterona (P4) foram determinadas por quimioluminiscencia imediatamente antes e a cada 6 horas após do tratamento com PGF2α até 24 horas. Posteriormente, a coleta realizou-se a cada 12 horas até às 48 horas. A frequência respiratória, cardíaca e temperatura retal foram mensuradas a cada 12 horas durante 7 dias; a temperatura vaginal foi determinada durante 7 dias com leituras a cada 10 minutos. A frequência respiratória, temperatura retal e vaginal foram superiores no ambiente de estresse calórico em relação ao termoneutro (P < 0.05); a frequência cardíaca não diferiu entre os dois ambientes (P > 0.05). As concentrações de P4 não diferiram (P > 0,05) entre os ambientes e seus respetivos tratamentos. Porém, na avaliação individual dos ambientes observou-se que, as vacas que receberam tratamento com ½XPGF2α independente do ambiente apresentaram uma diminuição inicial de P4 até às 18 horas com recuperação em momentos subsequentes, evidenciando uma luteólise parcial. Correlação positiva (r=0,5) foi evidenciada entre o tamanho do corpo lúteo e produção de...
Heat stress on luteolysis holstein non-lactating cow
Keywords: Luteólise; Corpo lúteo; Prostaglandinas; Progesterona; Vaca